Frontalis suspension for severe upper eyelid ptosis: advantages of the «sliding eight» technique - M.G. Kataev; M.A. Zakharova (Офтальмохирургия)
Relevance. Frontalis suspension is used in patients with severe upper eyelid ptosis. Despite the long history of the operation and multiple modifications, none of them gives a lifelong result. The use of suspensions sling materials that grow into tissue increases the surgical trauma during their removal if correction is necessary or recurrence of ptosis. Thus, the task is to choose a method of frontalis suspension, that would be easy to perform have an excellent result. Purpose. To evaluate the effectiveness, execution simplicity and reliability of the frontalis suspension using the «sliding eight» technique with polypropylene suture in patients with severe upper eyelid ptosis. Material and methods. A retrospective study of 84 patients (110 eyelids) with severe ptosis of upper eyelid. A frontalis suspension surgery for removing upper eyelid with the use of 4/0 polypropylene suture was performed in he all patients. The threads were passed into the thickness of the eyelids and brows through previously made skins incisions. The patients were divided into 3 groups: in the first group (25 patients) we used polypropylene frontalis suspension with two needles of the pentagon suspension designs, in the second group (28 patients) we used two polypropylene sutures in the form of two rectangles, in the third group (31 patients) we used the «sliding eight» technique.Results. In the first group, in 5 cases there was a deformation of the upper eyelid contour, in 2 cases a recurrence of ptosis was diagnosed. In the second group, the deformation of the upper eyelid contour was in 4 cases, and a recurrence of ptosis also developed in 2 patients. In the third group, we did not notice any deformation of the upper eyelid contour and palpebral folds. In two cases, recurrent ptosis was diagnosed. The operation time in the first group of patients was 30.21±5.048 min, in the second group – 32.97±3.68 min, in the third – 26.5±3.03 min. The duration of the operation was statistically significantly different between groups 1 and 3 and groups 2 and 3. Conclusion. Surgical treatment of severe ptosis of upper eyelid using the «sliding eight» technique has shown its effectiveness, ease of execution and reliability. This elegant technique minimizes postoperative complications in the form of asymmetry in the position of the upper eyelid, is easy to perform, leaves virtually no scarring, and can be repeated without significant surgical trauma.